Kedudukan Feminisme Dalam Islam menurut KH. Husein Muhammad - Refa Choirur Rizki; Tion Iswanto; Ika Sakiyya Apdi; Nurfaizah; Abdul Fadhil (Jurnal Ilmu Pendidikan dan Sosial, 2025)
KH. Husein Muhammad is one of the many religious figures who support feminism in Indonesia who uses the interpretation of the Qur'an as its basis. Feminism glorified by Husein Muhammad is not a bad connotation of feminism or only on gender, but rather a movement to create awareness about justice and discrimination regardless of gender. Feminism activists are not only women, but also men who want to fight for gender equality. This study aims to explore the position of gender equality in Islam according to KH. Husein Muhammad, a cleric who is an activist for gender equality based on Islamic values. This study uses a library research method with a qualitative descriptive analytical approach and content analysis. K.H. Husein Muhammad's thoughts show that Islam is a religion that upholds the values ​​of justice and gender equality. Discrimination against women that often occurs in society is not something taught by Islam, but rather the result of religious interpretations influenced by patriarchal culture. Therefore, efforts are needed to reinterpret religious texts with a more critical, contextual, and inclusive approach to realize gender justice in Islam